Training environment and vitamin D status in athletes - Peeling, P.; Fulton, S. K.; Binnie, M.; Goodman, C. (International Journal of Sports Medicine, 2013)
This study assessed the associations between gender, anthropometry, predominant training environment and Vitamin D status in 72 elite athletes. Additionally, any links between Vitamin D status and recent injury/health status, or sun protection practices were investigated. Athletes underwent an anthropometric assessment and provided venous blood samples for the determination of 25-hydroxyvitamin D (25(OH)D), the accepted biological marker of Vitamin D status. Finally, athletes completed a questionnaire relating to their recent training and injury history, and their sun protection practices. The athlete cohort were divided by predominant training environment as either indoor, outdoor, or mixed training environment athletes. The average (±SD) 25(OH)D levels of the group were 111±37 nmol/L, with the indoor training group (90±28 nmol/L) significantly lower than the outdoor (131±35 nmol/L), and mixed (133±29 nmol/L) training groups (p=0.0001). Anthropometrical measures were positively associated with 25(OH)D levels; however, recent injury status or sun protection practice showed no association. Given the significant differences in 25(OH)D levels between the outdoor and indoor predominant training environments, coaches of indoor athletes may wish to monitor their athletes' Vitamin D levels throughout the year, in order to avoid any possibilities of a deficiency occurring.